Aplikasi IT Support Work Orders Berbasis Web Dalam Rangka Menuju Sidoarjo Smart City - Aljunza, Marshal Sheva; Findawati, Yulian; Fitrani, Arif Senja; Kautsar, Irwan Alnarus (Infotek: Jurnal Informatika dan Teknologi, 2024)
One important aspect in supporting the smart city concept is adequate information technology infrastructure. The Sidoarjo district government has made many innovations in making this happen, one of which is the construction of an intranet and internet network using fiber optics which is centered in the Data Center and managed by the Sidoarjo District Communication and Information Center. As a work unit in the field of ICT infrastructure and security at the Sidoarjo Regency Diskominfo, it is responsible for serving reports from the OPD (Regional Apparatus Organization) regarding intranet and internet network problems in the Sidoarjo regency environment. However, the reporting system used is still very simple and manual. The aim of this research is to design and build a web-based system that functions as a complaint, documenting work, and reporting handling related to intranet and internet network problems at the OPD in Sidoarjo Regency. In collecting data, this research used qualitative methods. Meanwhile, system development uses the System Development Life Cycle (SDLC) method with waterfall model, and uses Unified Modeling Language (UML) and Entity Relationship Diagram (ERD) as system modeling. This application was built using PHP with the CodeIgniter framework and MySQL. The results of this research show that the system makes it easier for related parties to make complaints, document work, and report handling.